2009
DOI: 10.1128/iai.00718-08
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-Kinase-Dependent Inhibition of Dendritic Cell Interleukin-12 Production byGiardia lamblia

Abstract: Dendritic cell interactions with pathogenic microbes initiate and direct the development of subsequent adaptive responses. The protozoan pathogen Giardia lamblia infects the mammalian small intestine, leading to nutrient malabsorption and diarrhea but rarely causing inflammation. In order to begin to understand how the innate immune system responds to this parasite and shapes the eventual adaptive response, we examined the interaction between parasites and murine bone marrow-derived dendritic cells (DCs). DCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 51 publications
7
73
6
Order By: Relevance
“…The mechanisms driving this response are poorly understood, and the clinical studies did not exclude the presence of coinfecting helminths, which is associated with both mucosal eosinophils and susceptibility to G. lamblia (46). Acute Giardia infection with axenic trophozoites in mice does not demonstrate a robust inflammatory response (46), consistent with in vitro findings of suppressed DC cytokine production following exposure to Giardia or Giardia products in vitro (47). G. lamblia contains a biologically unique β-1,3 GalNAc homopolymer in its cyst wall (48), which in our cyst challenge model could partially explain why a different immune response was seen.…”
Section: Discussionsupporting
confidence: 59%
“…The mechanisms driving this response are poorly understood, and the clinical studies did not exclude the presence of coinfecting helminths, which is associated with both mucosal eosinophils and susceptibility to G. lamblia (46). Acute Giardia infection with axenic trophozoites in mice does not demonstrate a robust inflammatory response (46), consistent with in vitro findings of suppressed DC cytokine production following exposure to Giardia or Giardia products in vitro (47). G. lamblia contains a biologically unique β-1,3 GalNAc homopolymer in its cyst wall (48), which in our cyst challenge model could partially explain why a different immune response was seen.…”
Section: Discussionsupporting
confidence: 59%
“…Our laboratory previously showed that dendritic cells responded to parasite extracts by upregulating the expression of surface molecules, including CD40, CD80, and CD86, but that very little cytokine production was induced. Indeed, parasite extracts actually blocked IL-12 production in response to several TLR agonists, although IL-10 production was enhanced (19). A recent report showed that the endoplasmic reticulum (ER) chaperone protein BiP from Giardia could signal through TLRs, but like our own studies with dendritic cells, extremely high levels of protein were required to detect a response (39).…”
Section: Discussionmentioning
confidence: 94%
“…In vitro macrophages have been shown to be capable of ingesting Giardia, and we recently showed that macrophages accumulate in the lamina propria following infection (17,18). Bone marrow-derived dendritic cells mature in response to Giardia extracts, but cytokine production in response to Toll-like receptor (TLR) agonists is modulated toward interleukin-10 (IL-10) and away from IL-12 (19). Mast cells are also recruited following infection and are required for the efficient control of infection (20,21).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that mast cell hyperplasia occurs in the late stages of a Giardia infection or following parasite clearance (20,21) and that eosinophil accumulation may occur in vivo in an isolate-dependent manner (22). Furthermore, G. duodenalis parasite products have been shown to modulate dendritic cell responses to lipopolysaccharide (23,24), while separate studies have demonstrated that intestinal epithelial cells (IECs) exposed to Giardia trophozoites produce a unique chemokine profile (25). The need to investigate G. duodenalis's ability to modulate its host's proinflammatory responses is now apparent due to data collected from in vivo animal and human studies.…”
Section: G Iardia Duodenalis (Syn G Intestinalis G Lamblia)mentioning
confidence: 99%